Assessment, Interaction and Technology in Distance Education: A Netnographic Study at a Brazilian Virtual University - Édison Trombeta de Oliveira (Open Praxis, 2021)
Netnography is a research procedure to analyse people inserted in digital communities applied, in this research, at Virtual University of the State of São Paulo, the first Brazilian public institution that offers only distance education. The aim of this paper is to know what happens in the course Calculus III, of the undergraduate in Physics, with the interaction, assessment and technology, by applying netnography in forums. As a result, assessment is often referred to deal with the differences between what is expressed in the lessons from what is assessed. For interaction, it was verified that only 10% of the students participated in the forums, a cornerstone for the online interaction. Finally, it was seen that the technology can facilitate learning, as long as they are added in an intentional way. It can be seen that the netnography can bring relevant elements to analyse contexts of distance education.